Molecular tunability of surface-functionalized metal nanocrystals for selective electrochemical CO2 reduction. Issue 44 (27th September 2019) - Pankhurst, James R.; Guntern, Yannick T.; Mensi, Mounir; Buonsanti, Raffaella
Abstract : Disubstituted imidazolium compounds are used as ligands to promote the CO2 RR at the surface of Ag nanocrystal catalysts. Catalyst performance is fine-tuned at the molecular scale through systematic variation of the imidazolium substituents. Abstract : Organic ligands are used in homogeneous catalysis to tune the metal center reactivity; in contrast, clean surfaces are usually preferred in heterogeneous catalysis. Herein, we demonstrate the potential of a molecular chemistry approach to develop efficient and selective heterogeneous catalysts in the electrochemical CO2 reduction reaction (CO2 RR). We have tailor-made imidazolium ligands to promote the CO2 RR at the surface of hybrid organic/inorganic electrode materials. We used silver nanocrystals for the inorganic component to obtain fundamental insights into the delicate tuning of the surface chemistry offered by these ligands. We reveal that modifying the electronic properties of the metal surface with anchor groups along with the solid/liquid interface with tail groups is crucial in obtaining selectivities (above 90% FE for CO), which are higher than the non-functionalized Ag nanocrystals. We also show that there is a unique dependency of the CO2 RR selectivity on the length of the hydrocarbon tail of these ligands, offering a new way to tune the interactions between the metal surface with the electrolyte and reactants.